Seasonal abundance of the Neotropic Cormorant (Phalacrocorax brasilianus) at Lagoa dos Patos estuary, Southern Brazil - Barquete, Viviane (2008)
Censuses of the Neotropic Cormorant (Phalacrocorax brasilianus) were carried out at a power tower near the mouth of Lagoa dos Patos estuary, southern Brazil, from November 2001 to October 2002. At this major roosting site, a total of 309 counts over 47 days of census were performed to estimate monthly variation in the abundance of the Neotropic Cormorant. The highest abundance occurred in January (1390 birds), and the lowest in May (117 birds). The tower was a roosting site for cormorants at night, which arrived around 15:30 h onward, with numbers increasing near dusk. Birds preferentially used the lower levels of the tower (including the concrete base and levels 1 and 2) throughout the year and this preference could be partially due to strong winds in the area. Migrating cormorants arrived at the estuary in winter and spring, increasing throughout the summer and severely decreasing in autumn months, when they probably moved to inland breeding grounds.